Group Investigation: Peningkatan Kualitas Proses Pembelajaran dan Hasil Belajar Geometri di SMP Negeri 1 Krangkeng Kabupaten Indramayu - Abdul Bashar (Jurnal Pendidikan Madrasah, 2023)
This study aims to determine the quality of the learning process and learning outcomes on geometry concept material using a group investigation learning model. This research is a Classroom Action Research (PTK) which is carried out in two cycles. The subjects of the study were students of Class VIII-A SMP Negeri 1 Krangkeng Indramayu Regency The results showed that the group investigation learning model could improve the quality of the learning process as shown by an increase in interest by 13.45% (cycle I: 70.34%, cycle II: 83.76%), and an increase in student learning outcomes by 14.48% (cycle I: 68.28%, cycle II: 82.76%).